It started with the Greeks [videorecording (DVD)] - Burke, James, 1936- (Day the universe changed., 2004)
Explains how the questioning, rational attitude of the ancient Greeks has continued through the centuries in the West and has led to constantly changing knowledge and discovery, thus creating conflict between these changes and inherently conservative institutions. Also discusses the thesis of the series that particularly important developments in the history of Western thought have produced corresponding changes in who we are.